2010
DOI: 10.1111/j.1365-2982.2010.01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancolonic spatiotemporal mapping reveals regional deficiencies in, and disorganization of colonic propagating pressure waves in severe constipation

Abstract: Pancolonic, 24 h, spatiotemporal pressure mapping readily identifies characteristic disorganization among consecutive PS, regions of diminished activity and absent or deficient fundamental motor patterns and responses to physiological stimuli. These features are all likely to be important in the pathophysiology of slow transit constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 36 publications
2
105
0
Order By: Relevance
“…In our study, we were not able to elicit any distension or electrical nerve stimulation response, as was possible in some, but not all, control (non-STC) specimens. Also, in the study by Dinning et al (6), it was found that in vivo there was a disorganization among consecutive propagating sequences and reduced responses to physiological stimuli. In support of this, we found no responses were evoked to intraluminal balloon distension or electrical stimulation of STC colons.…”
Section: Comparison Of the Characteristics Of Cmcs Recorded In Human mentioning
confidence: 99%
“…In our study, we were not able to elicit any distension or electrical nerve stimulation response, as was possible in some, but not all, control (non-STC) specimens. Also, in the study by Dinning et al (6), it was found that in vivo there was a disorganization among consecutive propagating sequences and reduced responses to physiological stimuli. In support of this, we found no responses were evoked to intraluminal balloon distension or electrical stimulation of STC colons.…”
Section: Comparison Of the Characteristics Of Cmcs Recorded In Human mentioning
confidence: 99%
“…As a result our understanding of normal pressure/flow relationships is still relatively simplistic [3]. Therefore while abnormal contractility is implicated in FGIDs [4][5][6], how these abnormalities relate to impaired flow remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated, vascularly perfused loop preparation for video recording and spatiotemporal mapping has also been applied to smaller species such as rat 33 . A recent study by Kuizenga et al is the first use of STmaps of video recorded motility patterns in ex vivo segments of human intestine 42 ; although, STmapping approaches have been applied to the analysis of manometric (pressure) recordings in humans in vivo 3,44 . The recorded motility patterns in human tissue are similar to those already recorded in animal models using similar techniques and validate the extension of this approach to human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These have ranged from the initial in vivo observations and descriptions of William Beaumont and of Walter Cannon to the more recent methods of measurement and interpretation of multisite recording of muscle tension, intraluminal pressure, and/or membrane potential (i.e., junctional potentials) [2][3][4][5][6] . These latter approaches provide a snapshot of overall motility patterns, but are limited by the number of sites of recording and the validity of interpolation of the data to areas in between the recording sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation